Examination of Opinions and Attitudes about Forensic DNA Database: Medical Students, Forensic Medicine Doctors and Clinical Geneticists - Özçalışkan Özdemir, Burcu; Aktaş, Ekin Özgür (The Bulletin of Legal Medicine, 2024)
Objective: In this study, it is aimed to evaluate forensic medicine and genetics specialists and residents, medical students and genetics PhD students’ opinions on purpose, management and use of data of the forensic DNA database and their perspectives on the bank.Methods: In this study, an online survey application was preferred. Five hundred sixty-eight questionnaires were evaluated, including 354 medical students, 73 forensic medicine specialists, 98 forensic medicine residents, 14 genetics specialists, 24 genetics residents, and 5 genetics PhD students. In the survey; sociodemographic characteristics, professional characteristics, opinions about which institution should manage if a forensic DNA bank is established in our country, whose information will be stored, and positive aspects and concerns about the database were asked.Results: 46.7% of the participants were female and 53.3% were male. The mean age was 25.88±8.20 years. Approximately 50% of the participants stated that the DNA information of convicts, suspects, and volunteers should be kept. It was determined that positive opinions were at a higher level than concerns. It was observed that the anxiety levels of the medical faculty students were higher than the other participants. It was found that the level of anxiety decreased as the age increased.Conclusion: It is necessary to support the questions in our study, which sheds light on the general attitude about DNA bank for forensic purposes, with samples reflecting the society.
Keywords: forensic dna database; forensic medicine; physician; genetic; questionnaire